2021
DOI: 10.3390/insects12070586
|View full text |Cite
|
Sign up to set email alerts
|

Insect-Based Feed Ingredients for Aquaculture: A Case Study for Their Acceptance in Greece

Abstract: Although the inclusion of insects in fish diets is officially allowed in the EU since 2017, insect-based aquafeeds have not been widely adopted by the European aquaculture sector. In order to investigate the perceptions related with adoption trends, it is critical to explore the beliefs of people associated with the aquaculture sector on the use of insects in farmed fish diets. A survey was conducted among 228 participants of an aquaculture conference to explore their perceptions on the inclusion of insect mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 50 publications
0
17
1
1
Order By: Relevance
“…A part from consumer acceptability and preferences, other analyses based on contingent valuation have retrieved consumers' willingness to pay for insects as food or feed: the analysis conducted by Giotis and Drichoutis (2021) on Greek consumers a negative Willingness to Pay for direct entomophagy, implying that consumers require a discount in order to purchase the product, and a higher acceptance for indirect consumption of insects; willingness to pay for insects as feed is also higher in the analysis of Ferrer Llagostera et al (2019), even though taste expectations are low. Interestingly enough, the Greek survey conducted by Rumbos et al (2021) considered both demand and supplyside perspectives. Their analysis shows that individuals are indeed aware of the environmental spillovers of insectbased feed, and display a positive attitude and willingness to consume fish fed with insects.…”
Section: Introductionmentioning
confidence: 99%
“…A part from consumer acceptability and preferences, other analyses based on contingent valuation have retrieved consumers' willingness to pay for insects as food or feed: the analysis conducted by Giotis and Drichoutis (2021) on Greek consumers a negative Willingness to Pay for direct entomophagy, implying that consumers require a discount in order to purchase the product, and a higher acceptance for indirect consumption of insects; willingness to pay for insects as feed is also higher in the analysis of Ferrer Llagostera et al (2019), even though taste expectations are low. Interestingly enough, the Greek survey conducted by Rumbos et al (2021) considered both demand and supplyside perspectives. Their analysis shows that individuals are indeed aware of the environmental spillovers of insectbased feed, and display a positive attitude and willingness to consume fish fed with insects.…”
Section: Introductionmentioning
confidence: 99%
“…However, the wider adoption of insect utilization in aquafeed will likely depend, to a larger extent, on aquaculture producers and consumer acceptance. Despite few existing studies investigating people's perception concerning the use of insects as feed ingredients, the majority of the aquatic animal product consumers have shown favourable responses for various reasons, including risk-free ( Popoff et al., 2017 ; Szendrő et al., 2020 ), sustainability considerations ( Verbeke et al., 2015 ; Rumbos et al., 2021 ), as well as availability and access to information about the products ( Baldi et al., 2021 ; Rumbos et al., 2021 ). Product awareness and information availability are considered the most important factors that could accelerate the acceptance and positive perception of aquatic products produced on insects-based feeds ( Baldi et al., 2021 ; Rumbos et al., 2021 ).…”
Section: Utilization In Aquafeedsmentioning
confidence: 99%
“…Researchers investigating the consumer attitude toward products obtained using insect meals in fish diets showed that consumers are willing to accept these products (Arru et al, 2022;Mancuso et al, 2016) and are sometimes even willing to pay a premium, in particular when they are aware of the positive impact on footprint and sustainability of aquaculture (Ferrer Llagostera et al, 2019;Rumbos et al, 2021). In this special issue, Baldi et al (2022) used psychometric variables to study the acceptability of fish fed insect meals and focused their investigation on new generations as they are often more likely to accept these products.…”
Section: Introducing the Special Issue 'Application Of Insect Ingredi...mentioning
confidence: 99%